ANALISIS TREND MODEL LITERASI DIGITAL DALAM PENDIDIKAN DASAR - Ramadhani, Fitri; Rukli, Rukli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the trends in digital literacy models in primary education as part of the 21st-century competencies that need to be developed from an early age. A descriptive quantitative approach using a survey method was applied, involving 19 fifth-grade students of SDN 260 Kampung Baru as the sample. Data were collected through closed-ended questionnaires and teacher interviews, focusing on four key indicators of digital literacy: information searching, hypertext navigation, content evaluation, and knowledge assembly. The results showed that 68.4% of students were at a moderate level of digital literacy, while 31.6% were at a high level. The challenges identified included limited abilities in evaluating digital content and insufficient technical skills in managing information. Teachers emphasized the importance of strengthening digital literacy through curriculum integration, teacher training, adequate facilities, and active parental involvement. This study recommends the development of structured digital literacy-based learning to shape students into critical, creative, and responsible users of technology